Progress in Fine Particle Plasmas - Mieno, Tetsu; Hayashi, Yasuaki; Xue, Kun (IntechOpen, 2020)
In the field of plasma physics, plasmas (including charged fine particles) have been actively studied for more than 40 years, and special features of wave phenomena, self-organizations of the particles, potential formations, fluid-like motions of the particles, generations of fine particles in the plasmas, etc. have been investigated. Here, these plasmas are called "fine particle plasmas", which are also called "dusty plasmas" and "complex plasmas". This book intends to provide the reader with the recent progress of studies of fine particle plasmas from the viewpoints of wide and interdisciplinary directions, such as self-organized fine particles, Coulomb crystal formation, behaviors of fine particles, their stability, and syntheses of nano-sized particles in reactive plasmas. Further, the phenomena of dense grain particles and the effects of massive neutrinos in galaxy clustering are included.